2015
DOI: 10.1007/s11999-014-4098-4
|View full text |Cite
|
Sign up to set email alerts
|

Topical Tranexamic Acid Does Not Affect Electrophysiologic or Neurovascular Sciatic Nerve Markers in an Animal Model

Abstract: Topical tranexamic acid is effective in decreasing patient blood loss during THA, and results from our in vivo rat model study suggest there may be no electrophysiologic and histologic effects on the sciatic nerve, with the numbers available, up to 1 month.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…There is an important experimental study to answer this question. Schwarzkopf et al [ 29 ] sought to examine the effect of the topical application of TXA on the sciatic nerve in rats. They exposed the sciatic nerve and then administered subtherapeutic (1 mg/kg), therapeutic (10 mg/kg), and supratherapeutic (100 mg/kg) concentrations of topical TXA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an important experimental study to answer this question. Schwarzkopf et al [ 29 ] sought to examine the effect of the topical application of TXA on the sciatic nerve in rats. They exposed the sciatic nerve and then administered subtherapeutic (1 mg/kg), therapeutic (10 mg/kg), and supratherapeutic (100 mg/kg) concentrations of topical TXA.…”
Section: Discussionmentioning
confidence: 99%
“…They exposed the sciatic nerve and then administered subtherapeutic (1 mg/kg), therapeutic (10 mg/kg), and supratherapeutic (100 mg/kg) concentrations of topical TXA. They suggested that there were no electrophysiologic and histologic effects on the sciatic nerve, for up to 1 month [ 29 ]. Since the spinal cord will be completely exposed after laminectomy, the dose of the TXA in the topical application becomes important; therefore, we would like to emphasize that topical application should be treated with caution.…”
Section: Discussionmentioning
confidence: 99%
“…First, the rats were anesthetized with 100 mg/kg intramuscular sodium ketamine hydrochloride (Alphamine, Egevet, 100 mg/mL) and 20 mg/kg intramuscular xylazine (Alfazyne, Egevet, 2%) using a 30 G needle. The therapeutic dose (10 mg/kg) was selected for the dose of TXA to be used topically and IV, and diluted accordingly [15,17]. The same amount of saline solution was also prepared to ensure standardization.…”
Section: Surgical Procedurementioning
confidence: 99%
“…Especially, the effects of TXA on cartilage have been heavily studied [13,14]. Periarticular tissues outside of the cartilage and their effects on the sciatic nerve have been included in different research as well [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…All rats were randomized into four groups by using sealed envelopes. Local tranexamic acid (Transamin 100 mg/ml, Teva İlaç, İstanbul) were determined on the basis of previously conducted studies: 1 mg/kg (D1 group), 10 mg/kg (D10 group), 100 mg/kg (D100 group), and no tranexamic acid (D0 group) 21) . Two rats in the D0 group died after the radiographic examination.…”
Section: Experimental Designmentioning
confidence: 99%